Eksplorasi Karakteristik Item Skala Psikologis yang Rentan terhadap Tipuan Respon - Wahyu Widhiarso; Retno Suhapti (Faculty of Psychology, Universitas Gadjah Mada, 2009)
This study investigates item characteristics in psychological scale that susceptible to faking response. We examine the difference scores of Self Description form between two conditions. In the first condition we instruct subject to complete the form honestly (honest condition). On the other hand, in the second condition we instruct subject complete the form to make they look as good as possible (faking condition). Result suggest that in the item attributes that susceptible to faking, the score on the faking condition was higher than honest condition because subject were enable to improve their scores. We found that item attributes that verifiable, continuous, actual, controllable, second‐third sources, and future oriented were persistent to faking response. However item attributes that non‐verifiable, dichotomous, perceptual, first hand source and recent oriented, were vulnerable to faking response.